Study on Electric Power Quality in Power System: Understanding Power Quality and Efficiency in a Power System (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Power supply is not adequate. For smooth running and operation of the machinery, the characteristics of supply voltage at all times are quite important. The efficiency of the power supply is dependent on the voltage characteristics. Power quality is referred to as the extent to which supply voltage characteristics correspond to the appropriate norm. The need to ensure good efficiency has become important in the ever growing usage of electronic power devices in domestic and commercial settings and critical appliances in the automatic production industries. This paper clarifies the quality of power and its challenges. We address the causes and implications of issues of power efficiency. Mitigation methods are presented for issues in power efficiency.